Undang-Undang di Malaysia dan Jaminan Hak Orang Kurang Upaya untuk Bekerja (Jurnal Pembangunan Sosial, 2016)
Convention on the Rights of Persons with Disabilities (CRPD) has been signed by Malaysian Government on 8 April 2008. It shows the desire and commitment of the Government of Malaysia to give recognition to the rights of People with Disabilities. The aim of this article is to review the rights to work for Persons with Disabilities under the Federal Constitution and Person with Disabilities Act 2008 in Malaysia. This study will use Legal studies as research methodology and it involved two types of method which is doctrine study of the law and socio-legal studies. The studies showed that the rights to work for PWDs in Malaysia stated as generally in the Federal Constitution and the rights has been detailed in Person With Disabilities Act 2008. The existence of the right to work exclusively under the Person With Disabilities Act 2008 makes those rights not only for normal people but it is also owned by the PWDs. However, the existence of legislation alone is not enough if followed by enforcement. Thus, the improvement in the law and its implementation should be further strengthened through several proposals suggested by this article. It is to ensure the rights of the PWDs to get the job be given serious attention by the community in line with the original purpose of Persons with Disabilities Act 2008 being created.